Three-dimensional radar for ATC training : effects on trainees’ performance and workload - Wo, Alvin Kwok Onn (2018)
Air travel has been growing in popularity and is expected to continue growing over the next few decades. Airspace is finite thus air traffic density will only increase, which would in turn increase the workload of ATCOs. Air traffic control is crucial in ensuring that conflicts between flights are avoided, and thus, ATCOs must always be able to function at peak performance. Currently, ATCOs work with two-dimensional radar screens which only display airspace in the top-down view. Altitude is presented as numbers, which ATCOs must perceive and interpret before forming a mental image of the airspace. The effort of having to do may increase the workload of ATCOs. Hence, 3D visualisations of airspace are proposed to help reduce the workload of ATCOs by freeing ATCOs from having to construct mental images. This project’s aim was to firstly, train and familiarise subjects with the use of a complementary 3D and 2D display to equip them with the confidence and skills to operate the set up for subsequent experiment scenarios conducted by other FYP students. The second aim was to examine the workload and performance variation along the duration of the training so that an appropriate training duration may be selected for future use. Subjective and physiological workload were measured using the NASA-TLX and EEG respectively, while performance was characterised by the fuel consumption of flights throughout the training. These parameters were compared across time and analysed for any significant variation. The analyses suggest that the different training durations had an insignificant effect on physiological workload and performance, while a strong positive correlation between subjective workload and radio traffic was found.